Animal Bodies in the Museum: Acts of Artmaking, Collective Knowledge, and Complex Conversation Around Museum Taxidermy - Le Gallais, Jacob (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2022)
This paper explores how critical acts of making during a participatory museum workshop and subsequent studio-based research-creation can inspire poly-vocal discourses around museum taxidermy as repositories of complex histories. Centred on four animals on display at the Redpath Museum, this research program sought to reanimate these animals and reposition their context within the museum space and the wider world. Through collaborative exploration and creative acts of making, art educators can engage and shape the discourse around taxidermied animal bodies, giving them new life as tools for teaching and learning in museum spaces.